Point Prevalence of Type 2 Diabetes Mellitus Patients among Different Specialties at MTI Khyber Teaching Hospital in Peshawar - Malik, Suleman Elahi; Haider, Iqbal; Akhtar Khattak, Romesa; Bibi, Sidra; Naeem, Hammad; Iqbal, Marhaba (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: The main goal of this research study was to analyze the profile and prevalence of type 2 diabetic patients admitted to the MTI Khyber Teaching Hospital, Peshawar. METHODOLOGY: A hospital-based point prevalence cross-sectional descriptive study was carried out as a pilot project in November 2022 at MTI Khyber Teaching Hospital, Peshawar, Pakistan. Patients satisfying the inclusion and exclusion criteria enrolled in the study, and a non-probability consecutive sampling technique was used. RESULTS: A total of 850 patients were admitted during the study period; out of them, 24.7% had type II diabetes mellitus (T2DM). The mean length of hospital stay was significantly high among T2DM patients (p <0.01). Moreover, there were statistically significant differences ?2(2) = 94.67, p <0.01, in the mode of admission among the T2DM patients, with fewer cases shifted from other units compared to ER and OPD. The antidiabetic regimen prescribed during the hospitalization included an oral antidiabetic regimen (36.9%), oral plus twice-daily insulin regimen (19.63%), and basal-bolus insulin (15.07%). CCU and ophthalmology ward had the highest proportion of admissions of T2DM patients (40% each). Patients were admitted for various indications; 11.0% were admitted due to diabetic foot ulcer, 9.5% for elective surgery, 9.55% had acute coronary syndrome (ACS), and 9.0% had diabetic kidney disease. Conclusion: Patients admitted exhibited a high prevalence of T2DM. We highlighted some of the substantial characteristics of these patients attending various specialties.